Prospects for Treatment of Idiopathic Pulmonary Fibrosis - R. N. Mustafin (Архивъ внутренней медицины)
Idiopathic pulmonary fibrosis (IPF) is a severe, progressive lung disease of unknown etiology with an average worldwide prevalence of 15 per 100,000. According to the etiology, IPF is classified into sporadic, syndromic, and familial cases. Sporadic cases refer to multifactorial diseases and are associated with age, viral infections, smoking and inhalation of dust, contact with chemicals and drugs, gastroesophageal reflux disease. There were revealed an association of sporadic IPF with allelic variants of the genes AKAP13, ATP11A, DPP9, DSP, IVD, IL1RN, FAM13A, MUC5B, SFTPC, SPPL2C, TERC, TERT, TOLLIP. Syndromal IPF develops in German-Pudlak syndrome. Familial cases of the disease are caused by mutations in the genes encoding surfactant (SFTPC), mucin (MUC5B), deadenylation nuclease (PARN), components of telomere functioning (RTEL1, TERC, TERT). In 2000, the American Thoracic Society recommended glucocorticoids and cytostatics for the treatment of ELISA in order to influence the inflammatory process due to the activation of fibroblasts and their accumulation in the extracellular matrix of the lungs. These recommendations are still used by many doctors, despite the publication of reliable data on the increased mortality and hospitalizations of IPF patients taking prednisolone and azathioprine. According to recent meta-analyzes, pirfenidone (an inhibitor of the synthesis of procollagen I and II growth factors) and nintenadib (a tyrosine kinase inhibitor) are the most effective treatments for IPF. Since genetic factors play an important role in the etiopathogenesis of the disease, it is promising to search for methods of targeted therapy for IPF using specific noncoding RNAs as targets, changes in the expression of which are not specific of other bronchopulmonary diseases. These RNAs include miR-9-5p, miR-27b, miR-153, miR-184, miR-326, miR-374, miR-489, miR-630, miR-1343 (decreased expression in IPF); miR-340, miR-424, miR-487b, miR-493, lncRNA AP003419.16, lncRNA AP003419.16 (increased expression in IPF).